Students' Difficulties in Learning English at Tunas Ilmu Islamic Junior High School - Julita Rafisya; Fadilaturrahmah Fadilaturrahmah (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to analyse the difficulties experienced by female students at Tunas Ilmu Islamic Junior High School in learning English. English is an important subject in the curriculum, but some students still show difficulties in understanding and using the language effectively. This study uses a qualitative descriptive method with observation, interviews and a questionnaire given to students. The initial results of the essay questionnaire show that 50% of students say they like English lessons, while the other 50% experience difficulties in learning. Meanwhile, the results of the multiple-choice questionnaire showed that students experienced three difficulties, namely difficulty reading sentences, understanding vocabulary, and understanding grammatical concepts. Learning difficulties are a problem that prevents students from following lessons as well as other students in general. Learning difficulties are commonly experienced by students. The results of the study show that the main difficulties students face are in speaking and listening skills, which are caused by a lack of vocabulary, low self-confidence, and limited exposure to English outside the classroom. Another contributing factor is the lack of variety in teaching methods. Therefore, this study is expected to serve as a basis for teachers to design more effective learning strategies that are tailored to the needs of students.